A taxonomic study of the genus Svistella Gorochov (Orthoptera, Gryllidae, Trigonidiinae) - He, Zhuqing; Li, Kai; Liu, Xianwei (Zootaxa, 2009)
A taxonomic study of the genus Svistella Gorochov, 1987 is presented. Six species are described, including three new species and a new combination. A key to species of the genus is given.